Group of interests in the political process of contemporary Ukrainian society - Ermak, Vladimir (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES)
Тhe basic theoretical and methodological approaches to the problem of groups of interest, developed in foreign and domestic politics, are analyzed. It is shown that groups of interest are the result of differentiation and complexity of the social system as a mechanism to optimize the processes in the system, to increase the degree of its resistance to the destabilizing influences, to embed to the social space legitimate channels of social tensions’ relieve. The activities of the major groups of interest in Ukraine are examined; mechanisms of their political influence are studied. It is revealed that in Ukraine is was formed almost the entire core of organized interests that successfully operate in the West – business associations, trade unions and various non-governmental organizations, etc. An active process of developing a mechanism of their effect on the state takes place. This is one of the most valuable phenomena of modern Ukrainian reality, as it reflects a process of self-organization of various social groups with their specific interests. However, most groups of interest are too weak to have strong impact on the formation and implementation of public policy. Further development of groups of interest, enhancing of their representativeness, and optimizing of their interaction with state institutions are important components of democratic development in Ukraine